The Routledge Handbook of Global Sustainability Education and Thinking for the 21st Century - Fricker, Aleryk; Cooper, Grant; Kilmartin-Lynch, Shannon; Sheffield, Rachel (2025)
The aim of this chapter is to explore an innovative professional learning and teaching model intended to promote First Nations’ perspectives of sustainability in Australian undergraduate courses. As part of the Yarning to Learn initiative, First Nations university educators facilitate yarning circles with non-Indigenous university educators. In these safe spaces, non-Indigenous university educators were supported to reflect on and evaluate spaces where First Nations’ voices could be heard, or amplified, through sustainability-related concepts. The program was trialled across three Australian universities: Wurundjeri (Naarm/Melbourne), Wadawurrung (Waurn Ponds) and Nyungar Countries (Boorloo/Perth). To the best of our knowledge, this model of professional learning is a first-of-a kind design, embracing yarning and yarning circles as spaces for sharing and reflecting on how to promote First Nations’ perspectives in our teaching. We draw on autoethnographic methodologies to explore both the experiences of the participating First Nations and non-Indigenous university educators. In this chapter, Yarning to Learn acts as a cross-cultural bridge to support decolonising knowledge and thinking relating to sustainability education, facilitating non-Indigenous university educators as they are mentored, supported, and by led by expert First Nations university educators. These initiatives support efforts to empower non-Indigenous university educators to decolonise teaching and promote undergraduates’ understandings of First Nations’ worldviews of caring for Country and associated sustainability-related concepts and practices.